THE PARATEXT IN EDITIONS OF “THE LITTLE PRINCE” IN BRAZILIAN SIGN LANGUAGE: AND THE (IN)VISIBILITY OF THE TRANSLATOR - Gomes Rodrigues Lima, Jocelma; Fonseca Campos Ribeiro, Nadia Maria; Ferreira da Silva, Rafael (Revista de Letras, 2025)
This article aims to promote a discussion about paratexts in translated literary works, more specifically translation into sign languages, which raises several questions not only about Translation Studies, but Education, Accessibility and Language Policies. The proposed work of analysis is “The Little Prince”, by Antoine de Saint-Exupéry, in two editions in Brazilian Sign Language (Libras), published in 2016. Guided by the questions “How is the translation presented?”, “What does the paratext show?” and “Does the translated text present itself as an obvious translation?”, this research focused on just one paratextual element: the position of the translator’s name in the work to verify whether there is a process of in/visibility of the translator. Based on Casanova (2021), Venuti (2021), Genette (2009), Torres (2011), Quadros and Segala (2015), Strobel (2008) and Mourao (2012), we discussed paratexts in translated books, the role played by translators, Literature available in Brazilian sign language, Deaf Literature, (in)visibility of the sign language translator.